The making and unmaking of Hashimoto's thyroiditis: On the mismatch between illness and disease. Results from an Italian study. (July 2023) - Cardano, Mario; Rossero, Eleonora
The diagnostic process in contemporary medical practice is increasingly technical, specialised and relying on population-based ranges of biological normalcy. Disease is defined according to a hierarchy of evidence that privileges specialist knowledge and marginalises subjective experiences of illness. Medical and individual definitions of the situation can conflict in two ways: (i) a diagnosis is made in the absence of symptoms, (ii) individual suffering does not constitute 'real' disease if it is not validated by scientific evidence. This article investigates how the discrepancy between specialist and embodied knowledge is experienced and tentatively solved by patients' self-narratives. Starting from the analysis of 22 in-depth interviews with people affected by autoimmune diseases, we focus on the subgroup affected by Hashimoto's thyroiditis. Applying the most-different-systems design, we confront two flesh-and-blood ideal-types of illness narratives characterised by a mismatch between illness and disease. Their diagnostic trajectories are outlined and discussed as poles of a continuum of experiences resulting from different configurations of medical evidence of disease and subjective evidence of illness.